Student Support Services in the Ethiopian School System: Grades Four, Eight, Ten and Twelve in Focus - Admas, Fantahun; Teferra, Tirussew (The Ethiopian Journal of Education, 2024)
Student support services are key activities carried out by schools in order to improve students’ academic and non-academic skills. Students at various grade levels who received support from their respective schools tend to achieve and adjust better than those who did not have such an experience. This study was conducted to survey the support services students receive in Ethiopian schools and examine the availability, adequacy and importance of these services. To serve this purpose, a survey research design was employed. A total of 2243 students from grades four, eight, ten and twelve participated in the study from Amhara and Gambella regions, and Addis Ababa city administration. Multistage sampling technique was employed to select the participants. A questionnaire containing demographic characteristics and support services such as academic areas, counseling, material, special needs, health care, extra-curricular activities, physical school situations and parental involvement was employed to gather empirical data. The collected data were analyzed using descriptive statistics. The findings of the study showed that though over 50% of participants of the study indicated the presence of the services, they disclosed the inadequacy of the support services. However, a considerable number of students indicated the absence of such services and at the same time expressed the need for such services at all levels. Based on the findings, implications of the study are indicated.